The role of financial knowledge and financial literacy in student financial management - Titin, Titin; Marselina, Sely; Patimah, Sadah; Haryadi, Didit; Wahyudi (Trigin Publisher, 2024)
A country's high level of finance will encourage the development of its economy. Internal and external factors cause high and low financial management behavior. This study aims to develop a model that examines the three variables that the author has analyzed to determine the factors that can improve student financial management. This study used the associative descriptive quantitative method with a population of 103 respondents drawn into a sample of 72 respondents with a purposive sampling technique using non-probability sampling, using a purposive sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The first hypothesis shows that financial knowledge does not significantly affect student financial management, and the second hypothesis is that financial literacy variables have a significant effect on student financial management. The third hypothesis is that financial knowledge and literacy can affect student financial management. This research is expected to make theoretical contributions to the literature in this context, including in the context of financial and banking management